Assessment of meat products and saturated fatty acid intake in human diets. (September 2019) - Trbovic, D; Lakicevic, B; Petronijevic, R; Lukic, M; Jankovic, V; Petrovic, Z; Nastasijevic, I
Abstract: The World Health Organization (WHO) has released a guide to proper diet in which the food pyramid is presented. The food pyramid indicates graphically which types of food should be eaten daily. Changes in the diet of any population are slow and difficult to achieve. The aim of this study was to investigate: a) the fatty acid composition of processed meat products, and; b) the daily saturated fatty acid (SFA) content, as calculated by estimated consumption of processed meat products (meat pieces preserved in plastic casing by heat treatment) present in the Serbian market. Consumption of 100 g of preserved pork meat pieces per day equated to 4.64 g saturated fat or 23.20% of daily fat intake being saturated, while consumption of preserved poultry meat pieces would result in 1.73 g of saturated fat, or 8.65% of daily fat intake being saturated which is closer to the recommended daily intake of 10% of fats being saturated. Further research is needed to understand better the optimal combination of unsaturated fatty acids in these processed meat products and recommended daily intakes that should maintain and enhance the health status of consumers.